PENGARUH MODEL PEMBELAJARAN KONFLIK KOGNITIF TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI - Asep Sujana; Enjuh Juhaedi (Universitas Islam Nusantara, 2017)
This research is intended to know the extent of the influence of the application of Cognitive Conflict Learning Model to Improving Mathematical Understanding of Students of Class XI IPS SMA Mathla'ul Anwar Menes